Pension Systems in Europe. Case of Croatia - Jarosław Poteraj (Contemporary Economics)
The article presents an insight into the old age pension system in Croatia. The introduction is followed by four topic paragraphs: the general information about the country, the historical development of its pension system, the present situation, and challenges and foreseen changes. There, the author’s goal was to present both past and present solutions employed by the Croatian’s pension system, in search for ideas worth consideration in international comparisons. In the summary, the author highlights that Croatia is a country with great potential but at present it is difficult to identify solutions worth copying in other states.